Intensive Methods of Developing Students' Graphic Competencies in the Training of Competitive Personnel - Kahharov, Abduraxim Abdubannaevich; Rahimova, Gulnora Elyor qizi (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses the role of graphic sciences in the training of competitive personnel, their tasks and the importance of design work. Recommendations and suggestions were made on intensive methods of developing graphic competencies in students.